Online Learning Strategies during the Covid-19 Outbreak in the Pie Study Program on Campus: Strategi Pembelajaran Daring di Masa Wabah Covid-19 Pada Program Studi Pai Di Kampus - Uswatun Khasanah; Imam Fauji (Academia Open, 2022)
This article aims to add to the scientific treasures of online learning strategies during the covid-19 outbreak in the PAI study program at Muhammadiyah University of Sidoarjo, making it easier for readers to find references about this article. The research approach in this article is descriptive qualitative with data obtained from observations, interviews and documentation in the field. The results of this study found that the online learning strategy during the covid-19 outbreak in the PAI study program at the University of Muhammadiyah Sidoarjo, namely learning focused on online learning applications with a student center approach, teacher center and stimulus response and paying attention to 4 stages, namely determining time management, preparing technology needed, study seriously and maintain communication.